Chemokine CCL2 and its receptor CCR2 in the dorsal root ganglion contribute to oxaliplatin-induced mechanical hypersensitivity. Issue 7 (July 2018) - Illias, Amina M.; Gist, Andrea C.; Zhang, Haijun; Kosturakis, Alyssa K.; Dougherty, Patrick M.
Abstract : Abstract: Activation of innate immune mechanisms within the dorsal root ganglion and spinal dorsal horn has been shown to play a key role in the development of neuropathic pain including paclitaxel-related chemotherapy-induced peripheral neuropathy (CIPN). Here, we tested whether similar mechanisms are generalizable to oxaliplatin-induced CIPN. After a single intraperitoneal injection of 3 mg/kg oxaliplatin, mechanical withdrawal threshold and the expression of C-C chemokine ligand 2 (CCL2) and its receptor, CCR2, in the dorsal root ganglion were measured by behavioral testing and immunohistochemical staining, respectively. Mechanical responsiveness increased from the first day after oxaliplatin injection and persisted until day 15, the last day of this experiment. Immunohistochemical showed that the expression of CCL2/CCR2 started to increase by 4 hours after oxaliplatin treatment, was significantly increased at day 4, and then both signals became normalized by day 15. Cotreatment with intrathecal anti-CCL2 antibodies prevented the development of oxaliplatin-induced mechanical hyperresponsiveness, and transiently reversed established hyperalgesia when given 1 week after chemotherapy. This is the first study to demonstrate CCL2/CCR2 signaling in a model of oxaliplatin-related CIPN; and it further shows that blocking of this signal can attenuate the development of oxaliplatin-induced mechanical hyperalgesia. Activation of innate immune mechanisms may therefore be a generalized basis for CIPN irrespective of the specific class of agent. Abstract : A novel signaling pathway mediated by CCL2/CCR2 is induced by a single dose of oxaliplatin within the dorsal root ganglion; and the blocking of this signal attenuates oxaliplatin-induced mechanical allodynia.